2019
DOI: 10.1016/j.jtcvs.2018.10.135
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcome and graft patency of radial artery and saphenous vein grafts in multiple arterial revascularization

Abstract: Objective: The long-term benefits of multiple arterial revascularization (MAR) in coronary artery bypass grafting remain uncertain. The aim of this study was to investigate the clinical outcome, graft patency, and need for subsequent target revascularization of radial artery (RA) versus saphenous vein graft in patients undergoing MAR in both patient-and graft-specific analyses.Methods: Between 2001 and 2016, we followed 1654 patients over a median of 7.4 years in a prospective, longitudinal study. Major advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 36 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…However, GEA use is not very popular despite the good outcome observed in several studies [17,18]. Ruttmann E [19]. for RADIAL investigators has reported better survival and outcome regarding patency and the need for target-vessel revascularization of the radial artery graft in comparison with saphenous vein graft; we have had no experience with radial artery grafting and it was never used in this series because we have privileged in situ grafts.…”
Section: Discussionmentioning
confidence: 91%
“…However, GEA use is not very popular despite the good outcome observed in several studies [17,18]. Ruttmann E [19]. for RADIAL investigators has reported better survival and outcome regarding patency and the need for target-vessel revascularization of the radial artery graft in comparison with saphenous vein graft; we have had no experience with radial artery grafting and it was never used in this series because we have privileged in situ grafts.…”
Section: Discussionmentioning
confidence: 91%
“…However, GEA use is not very popular despite the good outcome observed in several studies [17,18]. Ruttmann E. [19] for RADIAL investigators has reported better survival and outcome regarding patency and the need for target-vessel revascularization of the radial artery graft in comparison with saphenous vein graft; we have had no experience with radial artery grafting and it was never used in this series because we have privileged in situ grafts . We did not test if the impact of ITA anastomosis and GEA anastomosis could be different, rst because such evaluation is not appropriate without concomitant study of the patency and second because the target vessels were de nitively different; however the contribution of sequential ITA graft was found determinant, underlying the bene t of additional bypass targets revascularized with an ITA.…”
Section: Discussionmentioning
confidence: 91%
“…However, GEA use is not very popular despite the good outcome observed in several studies [17,18]. Ruttmann E. [19] for RADIAL investigators has reported better survival and outcome regarding patency and the need for targetvessel revascularization of the radial artery graft in comparison with saphenous vein graft; we have had no experience with radial artery grafting and it was never used in this series because we have privileged in situ grafts. We did not test if the impact of ITA anastomosis and GEA anastomosis could be different, rst because such evaluation is not appropriate without concomitant study of the patency and second because the target vessels were de nitively different; however the contribution of sequential ITA graft was found determinant, underlying the bene t of additional bypass targets revascularized with an ITA.…”
Section: Discussionmentioning
confidence: 92%